Near-zero refractive index photonics - Liberal, Iñigo; Engheta, Nader (Nature photonics, 2017)
The underlying principles and unique optical applications of structures exhibiting near-zero dielectric permittivity and/or magnetic permeability are reviewed. The timely relevance to nonlinear, non-reciprocal and non-local effects is highlighted. Structures with near-zero parameters (for example, media with near-zero relative permittivity and/or relative permeability, and thus a near-zero refractive index) exhibit a number of unique features, such as the decoupling of spatial and temporal field variations, which enable the exploration of qualitatively different wave dynamics. This Review summarizes the underlying principles and salient features, physical realizations and technological potential of these structures. In doing so, we revisit their distinctive impact on multiple optical processes, including scattering, guiding, trapping and emission of light. Their role in emphasizing secondary responses of matter such as nonlinear, non-reciprocal and non-local effects is also discussed.